Ordenamiento y caracterización faunisitica del Cretacico superior del Grupo Chubut, Cuenca del Golfo San Jorge, Argentina - Casal, Gabriel (2016)
The Chubut Group, central Patagonia, Argentina, is characterized by a lacustrine and fluvial-lacustrine system with variable participation of volcanic ash. This group includes the Bajo Barreal Formation (Cenomanian-Turonian) and a recently nested new lithostratigraphic unit, the Lago Colhué Huapi Formation (Coniacian-Maastrichtian). The Lago Colhué Huapi Formation overlies the Bajo Barreal Formation. These sedimentary units preserve a rich and diverse vertebrate fossil record including, among others, representatives of Crocodylomorpha, Testudines, Pterosauria and abundant Dinosauria. Nevertheless, the stratigraphic position of several of its taxa has been historically controversial. The unclear stratigraphic provenance of these taxa difficults the correct interpretation of the relationships with other Patagonian and South American basins. In this context, we present a detailed stratigraphic study to clarify the position of the vertebrate fossils of both Late Cretaceous formations . We also discuss the implications of this faunistic arrangement in terms of vertebrate evolution and paleobiogeography. Finally, this study broadens our knowledge on the fossil fauna of these units and therefore the vertebrate assemblages of central Patagonia.